Compromise point incorporating trade-off ratio in multi-objective optimization - Kitayama, Satoshi; Yamazaki, Koetsu (Applied soft computing, 2012)
[Display omitted] ► The numerical calculation of the trade-off ratio was proposed. ► Compromise point considering the trade-off ratio is numerically determined. ► The aspiration level to obtain the compromise point is proposed. Through numerical examples, the validity is examined. The aims of multi-objective optimization are (1) to find pareto-optimal solutions and (2) to analyze the trade-off between conflicting objectives. This paper proposes an interactive method for solving multi-objective optimization problems using the satisficing trade-off method (STOM). In particular, we introduce a trade-off matrix to quantitatively analyze the trade-off between conflicting objectives. Each element of the trade-off matrix consists of a projection matrix of active constraints and gradients of objective functions. In addition, the compromise point and the compromise solution incorporating the trade-off ratio that the decision-maker desires are defined in this paper. The technique to obtain the compromise point is proposed in this paper. Through numerical examples, the validity proposed method is examined.